2012
DOI: 10.1016/j.fishres.2011.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Changes in egg buoyancy during development and its effects on the vertical distribution of anchovy eggs

Abstract: a b s t r a c tSmall pelagic fish populations exhibit reproductive strategies resulting from past natural selection pressure, by which certain traits become more or less common in a population, allowing them to adapt and become better suited to certain habitats. One such adaptation is the buoyancy of eggs, which is observed as density changes during development. This is an important issue in fisheries and modeling science, as it affects the vertical distribution of eggs and, therefore, egg transport. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 40 publications
(74 reference statements)
2
41
0
Order By: Relevance
“…The buoyancy of the eggs released is also an important quality measure that is often ignored. Egg buoyancy and changes in buoyancy throughout egg development can have important consequences for dispersal and survival (Ospina-Álvarez et al 2012). Recently, a numerical simulation of eggs and larval dispersal in the area of study showed that large differences in the probability of remaining in the littoral zone occurred at spatial scales of 20 km (Basterretxea et al 2012).…”
Section: Egg Buoyancy Through Embryonic Development (Objective No 3)mentioning
confidence: 99%
“…The buoyancy of the eggs released is also an important quality measure that is often ignored. Egg buoyancy and changes in buoyancy throughout egg development can have important consequences for dispersal and survival (Ospina-Álvarez et al 2012). Recently, a numerical simulation of eggs and larval dispersal in the area of study showed that large differences in the probability of remaining in the littoral zone occurred at spatial scales of 20 km (Basterretxea et al 2012).…”
Section: Egg Buoyancy Through Embryonic Development (Objective No 3)mentioning
confidence: 99%
“…One study [44] involved capture of live eggs and transfer to different salinities for buoyancy measurements; numerical codes for these data are shown with a “T” in panels. Symbols represent different populations within following species: Cynoscion nebulosus , spotted seatrout (lab-fertilised) [69]: 1– Matagorda Bay, Texas; 2– Upper Laguna Madre, Texas; Enchelyopus cimbrius, fourbeard rockling (all eggs captured at sea): 1 =  Baltic Sea, Gotland Basin [104], 2 =  Baltic Sea, Kiel Bay (field-captured and transfered) [44], 3 =  Conception Bay, Newfoundland, Canada [105], 4 =  Placentia Bay, Newfoundland, Canada [106] with hydrographic data from [107], 5 =  Tracadie Bay offshore, Gulf of St. Lawrence, Canada [108]; Engraulis encrasicolus, anchovy, (all eggs captured at sea): 1– Bay of Biscay [109], [110]; 2– Black Sea [20], [111] with hydrographic data from [112], 3 - Gulf of Lyons [54]; 4– NW Africa-Morocco [113], 5– Po River plume, northern Adriatic Sea [114]; Gadus morhua, cod: 1– Arcto-Norwegian cod: Lofoten (lab-fertilised) [25]; 2 - eastern Baltic (lab-fertilised) [24], [26]; 3– Baltic Sea, Gotland Basin (lab-fertilised) [25], [26]); 4 and 4-T –Baltic Sea, Kiel Bay (field-captured and transferred) [44], 5– Baltic Sea, ICES SD 23 (lab-fertilised) [26], 6– Baltic Sea, ICES SD 24 (lab-fertilised) [26], 7– Baltic Sea ICES SD 25 (lab-fertilised) [26], 9– Baltic Sea, ICES SD 26 (field-captured) [104], 10– Conception Bay, Newfoundland, Canada (field-captured) [105], 11– Gulf of St. Lawrence, Canada (field-captured) [115], 12– Grand Banks, Newfoundland, Canada (field-fertilised) [116], 13– Gullmarenfjord, Kattegat, western Sweden (lab-fertilised) [26], 14 - inshore Newfoundland, Canada (lab-fertilised) [116], 15– Norwegian coastal cod (lab-fertilised) [23]; 16– Norwegian coastal cod, Helgeland, Norway (field-captured) [117], 17- Norwegian coastal cod, Øygården, Norway (field-captured) [117], 18 - Norwegian coastal cod, Porsanger, Norway (field-captured) [117]; 19– Norwegian coastal cod, Tysfjord, Norway (field-captured) [117], 20– Tracadie Bay offshore, Gulf of...…”
Section: Resultsmentioning
confidence: 99%
“…cod 97%) compared to marine cod eggs (93%), due to the increased water uptake during final oocyte maturation which is aquaporin-mediated (Thorsen et al, 1996;Craik and Harvey, 1987;Fabra et al, 2005). Recent studies on cod (Jung et al, 2012a,b;Guðmundsdóttir, 2013) and anchovy (Ospina-Álvarez et al, 2012) found egg buoyancy increasing and decreasing towards the end of the ontogenetic development, respectively. Changes in biochemical components are likely to be the main cause that accounts for decreased specific gravity towards hatching (Jung et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in biochemical components are likely to be the main cause that accounts for decreased specific gravity towards hatching (Jung et al, 2012b). Several studies recommended incorporating such detailed density changes into the modeling of potential drift routes (Myksvoll et al, 2011;Jung et al, 2012a,b;Ospina-Álvarez et al, 2012). For Norwegian coastal cod, such density adjustment was applied using linear models considering development time and temperature (Myksvoll et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation